(untitled) (Sciences & Technology. A, exactes sciences, 2001)
The purpose of this paper is to investigate the path integral representation of Dirac propagator by considering the case of the free spinning particle. Thanks to the introduction of a suitable transformation, the domain of integrations over Grassmannian variables becomes free from the restriction and then via the Grassmannian sources, the integration over relative velocities are readily carried out. Such a way of calculation allows us to get the explicit spinor structure of the propagator.